Polarization-Angle SPDC Spectrum and its Effect on Generated Photon States - Agapov A.; Gostev P.; Magnitskya S.; Firsov V.; Frolovtsev D. (EPJ Web of Conferences, 2015)
Analytical formulas for vector components of the polarization vector of spontaneous parametric down-conversion (SPDC) radiation in the degenerated regime and its dependencies on the angle between the principal sections for the pump and SPDC rays are derived. The entanglement losses in the double-crystal SPDC scheme caused by the Migdal effect are analyzed. The analytical expressions are illustrated numerically for the case of BBO crystal.